THERMAL EXPANSION OF TERNARY MOLYBDATE K5[Mn0.5Zr1.5](MoO4)6 - E.V. Kovtunets; Yu.L. Tushinova; A.V. Logvinova; Ts.T. Bazarova; B.G. Bazarov (Вестник ВСГУТУ, 2024)
Compound K5[Mn0.5Zr1.5](MoO4)6 was obtained by solid-phase synthesis. Phase identification and calculation of unit cell parameters were carried out by Rietveld method. Compound crystallizes in trigonal syngony with space group R3c, a = 10.6026(1); c = 37.6253(5) Å; V = 3663.0(1) Å3. Thermal behavior was studied by high-temperature powder X-ray diffraction in temperature range of 30–500°C. Ternary molybdate K5[Mn0.5Zr1.5](MoO4)6 is a material with high thermal expansion (αV = 43x10–6 °C–1) and is characterized by significant anisotropy in crystallographic с-direction.